Efforts to Improve Story Text Writing Skills Review Biography by Developing Materials Interactive Multimedia Learning for Tanjung Balai 1 Senior High School - Nita Marpaung, Prama; Sutikno (International Journal of Educational Research Excellence (IJERE), 2025)
Based on interviews with students and teachers, interactive learning media are needed in the teaching and learning process. Multimedia-based learning media on biographical retelling text material is expected to foster students' interest and curiosity because, in addition to containing material, it is also equipped with music, pictures, and videos that are easy to understand. This study aims to determine the development of interactive multimedia-based learning media in biographical retelling texts for students in class X State Senior High School 1 Tanjung Balai Academic Year 2024-2025. The study uses (R&D) method was used in this study. The subjects of the study were students in class X State Senior High School 1 Tanjung Balai Academic Year 2024-2025. Based on the product effectiveness test conducted on the media, it is known that interactive multimedia-based learning media are effective in the learning process. Based on the results of the product effectiveness test, interactive multimedia-based learning media had an effectiveness of 84.28% with a very good category. Based on the results of the test conducted, it is known that the learning outcomes of students who use multimedia-based learning media are higher than those of students who do not use multimedia-based learning media. The average value of students who study using interactive multimedia-based learning media has an average value of 84.3 while students who study using without interactive multimedia-based learning media get an average value of 65.1.